2016
DOI: 10.1111/trf.13777
|View full text |Cite
|
Sign up to set email alerts
|

Prospective randomized and crossover comparison of two apheresis machines for peripheral blood stem cell collection: a multicenter study

Abstract: The Optia is safe and more efficient in the PBSC collection compared with the Spectra-Auto.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 27 publications
1
8
1
Order By: Relevance
“…A review and a more recent randomized study concluded that the Spectra Optia has comparable apheresis yields with the Spectra‐Auto, although collection efficiency was significantly higher in the Spectra Optia. Almost all the patients in our study were collected with the same apheresis system, further decreasing variation due to collection devices.…”
Section: Discussionmentioning
confidence: 99%
“…A review and a more recent randomized study concluded that the Spectra Optia has comparable apheresis yields with the Spectra‐Auto, although collection efficiency was significantly higher in the Spectra Optia. Almost all the patients in our study were collected with the same apheresis system, further decreasing variation due to collection devices.…”
Section: Discussionmentioning
confidence: 99%
“…Allogeneic (allo‐) or autologous (auto‐) hematopoietic stem cell (HSC) transplantation (HSCT), which includes peripheral blood stem cell (PBSC) transplantation (PBSCT), is a curative treatment for various hematologic disorders. For PBSCT, HSCs are mobilized by granulocyte colony‐stimulating factor and/or plerixafor and are collected by apheresis 1–3 . The apheresis‐collected product is cryopreserved until the time of infusion for almost all patients preparing for auto‐PBSCT and most patients waiting for allo‐PBSCT, whereas it is immediately infused without cryopreservation occasionally in allo‐PBSCT recipients 4,5 .…”
Section: Introductionmentioning
confidence: 99%
“…For PBSCT, HSCs are mobilized by granulocyte colony-stimulating factor and/or plerixafor and are collected by apheresis. [1][2][3] The apheresis-collected product is cryopreserved until the time of infusion for almost all patients preparing for auto-PBSCT and most patients waiting for allo-PBSCT, whereas it is immediately infused without cryopreservation occasionally in allo-PBSCT recipients. 4,5 For cryopreservation, an appropriate dose of cryoprotectant is added to the PBSC product based on its volume for prevention of cellular injuries, such as intraand extracellular ice formation and cell dehydration, due to storage at temperatures below À80°C or with liquid/ vapor nitrogen.…”
Section: Introductionmentioning
confidence: 99%
“…8 In recent years, few studies have evaluated the operation and differences between these two systems, in different populations and with different results. [8][9][10][11][12][13] The aim of our study is to compare the efficacy in collecting hematopoietic progenitors cells with the OPTIA compared to the COBE, focusing on procedure efficiencies and quality of products in both autologous and allogeneic donations.…”
Section: Introductionmentioning
confidence: 99%